folositi metoda spargerii la: x²-7x+10. Va roog
Răspunsuri la întrebare
Răspuns de
14
x² - 5x - 2x + 10 = x· ( x -5) - 2·( x -5) = ( x -5) · ( x -2)
getatotan:
ok
Răspuns de
2
x^2-7x+10= x^2-5x-2x+10= x(x-5) -2(x-5) =(x-5)(x-2)
[tex]x^2-7x+10= x^2 -5x-2x+10 = x(x-5) -2(x-5) =(x-5)(x-2)[/tex]
[tex]x^2-7x+10 = x^2-7x+14-4 = (x^2-4) -7(x-2) \it =( x^2-2^2) - 7(x-2) = (x-2)(x+2)-7(x-2) =(x-2)( x+2)-7(x-2) = (x-2)(x+2-7) = (x-2)(x-5)[/tex]
[tex]x^2-7x+10= x^2 -5x-2x+10 = x(x-5) -2(x-5) =(x-5)(x-2)[/tex]
[tex]x^2-7x+10 = x^2-7x+14-4 = (x^2-4) -7(x-2) \it =( x^2-2^2) - 7(x-2) = (x-2)(x+2)-7(x-2) =(x-2)( x+2)-7(x-2) = (x-2)(x+2-7) = (x-2)(x-5)[/tex]
Alte întrebări interesante
Matematică,
9 ani în urmă
Matematică,
9 ani în urmă
Matematică,
9 ani în urmă
Matematică,
9 ani în urmă
Limba română,
9 ani în urmă
Matematică,
10 ani în urmă
Limba română,
10 ani în urmă